Aerobic exercise training prevents skeletal myopathy by myomiRs regulation in heart failure. (14th October 2021) - Pelozin, B R A; Rodrigues, L P; Arruda, B F T; Voltarelli, V A; Brum, P C; Oliveira, E D; Fernandes, T
Abstract: Introduction: Heart failure (HF) is the endpoint of systemic arterial hypertension. Exercise intolerance is a common symptom, partly due, to changes in the skeletal muscle mass (SM) and fiber type profile. Otherwise, aerobic exercise training (ET) has been used as an important non-pharmacological therapy in HF. MyomiRs are a muscle-specific class of miRNAs, which regulate genes that inhibiting the expression of proteins in pathological and physiological conditions controlling phenotypic changes in the SM, however little is known about these changes in ET-induced HF Purpose: To elucidate the molecular mechanisms of ET involved in the metabolic alterations of SM in HF rats of hypertensive etiology. Methods: The study was approved by the animal ethics committee (USP-No. 2020/01). 20 male rats, spontaneously hypertensive (SHR), and 10 Wistar Kyoto rats (WKY), SHR controls, nine-months-old, were divided into three groups: sedentary WKY (WKY-S), sedentary SHR (SHR-S), and trained (SHR-T). The ET consisted of swimming sessions with 60 minutes, 1x/day, 5x/week, for 10 weeks, with 5% of body overload. After ET protocol, blood pressure (BP), cardiac morphology and function (Echocardiography), exercise tolerance test, maximal oxygen uptake (VO2 peak), mitochondrial oxygen consumption (Oroboros), immunohistochemistry of the SM, expression of miRNAs (RT-qPCR) were evaluated. Statistical analyzes were performed by one-way ANOVA followed by the Tukey test. The results were expressed as mean ± standard error. Results: ET reduced blood pressure levels and cardiac dysfunction in SHR-T compared to SHR-S. The SHR-S group covered smaller distance in the exercise tolerance test (255±22 meters) compared to the WKY-S (419±19 meters, p<0.0001), however ET reestablished the exercise tolerance (SHR-T: 365±20 meters; SHR-S: p<0.001 and WKY-S: p>0.05). The HF induced changes in type I and II fibers composition (I: 73±0.6% and II: 24±0.9%), VO2 peak (50±1.5 mL kg –1 min –1 ), mitochondrial oxygen consumption (State 3: 3.0±0.2 nmol O2 min –1 mg protein –1 ) and myomiRs expression (miRNA-208b: 65±4%, -499: 73±5%, -1: 153±10%) in the soleus muscle of SHR-S compared to WKY-S (I: 94±0.6%, II: 6±0.6%, p<0.001; VO2 peak: 59±2.3 mL kg –1 min –1, p<0.01; State 3: 4.0±0.2 nmol O2 min –1 mg protein –1, p<0.05; miRNAs: p<0.01). ET minimized changes in metabolic profile by counteract the muscle fiber type switching, and the oxygen consumption impairment, and myomiRs expression dysregulation (I: 90±0.5%, II: 9±0.6%, SHR-S p<0.01; VO2 peak: 79±2.4 mL kg –1 min –1, SHR-S: p<0.0001; State 3: 5.45±0.32 nmol O2 min –1 mg protein –1, SHR-S: p<0.0001; miRNA-208b: 91±5%, -499: 106±8%, -1: 100±9%; SHR-S: p<0.01). Conclusions: ET reestablished structural and metabolic changes in SM, resulting from the progression of HF, through the regulation of myomiRs, improving exercise tolerance. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The Coordination for the Improvement of Higher Education Personnel (CAPES): Academic Excellence Program (Proex).